1994
DOI: 10.1111/j.1471-0528.1994.tb13581.x
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord blood gas analysis at delivery: a time for quality data

Abstract: Objectives To address the practical problems of routine umbilical cord blood sampling, to determine the ranges for pH, pCO2 and base deficit and to examine the relationships of these parameters between cord vessels. Design An observational study of umbilical cord artery and vein blood gas results. Setting A large district general hospital in the UK. Subject One thousand nine hundred and forty‐two cord results from 2013 consecutive pregnancies of 34 weeks or more gestation, monitored by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
176
5
20

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(214 citation statements)
references
References 29 publications
13
176
5
20
Order By: Relevance
“…Only pregnancies with singleton vertex presentations, complete information about all the investigated parameters, and validated cord blood samples, were included. The quality of paired umbilical arterial and venous blood samples was validated by excluding samples obtained from the same umbilical vessel according to the criteria that pH in the artery should be > 0.02 units lower than in the vein [6,7]. Single-vessel samples were excluded due to uncertain origin.…”
Section: Methodsmentioning
confidence: 99%
“…Only pregnancies with singleton vertex presentations, complete information about all the investigated parameters, and validated cord blood samples, were included. The quality of paired umbilical arterial and venous blood samples was validated by excluding samples obtained from the same umbilical vessel according to the criteria that pH in the artery should be > 0.02 units lower than in the vein [6,7]. Single-vessel samples were excluded due to uncertain origin.…”
Section: Methodsmentioning
confidence: 99%
“…It is therefore prudent to have normal blood gases on record for a baby who had a normal delivery but subsequently develops neurologic impairment, or even minor learning disabilities 1 . Authorities 2,3 have suggested that the routine collection of cord blood for blood gas analysis should include sampling from both artery and vein. Westgate et al 3 found that of 1798 paired samples, 350 (19.4%) had unphysiologic pH and carbon dioxide (CO 2 ) readings (compared with the artery, the oxygenated umbilical vein must have a higher pH and lower CO 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cases were excluded from UAB pH analysis if paired samples were not obtained, if pH values between the two samples differed by less than 0.03 units or if values of partial pressure of CO 2 between the two samples differed by less than 7.5 mmHg. [9][10][11] Apgar scores were evaluated by the health professional responsible for immediate neonatal support, in the majority of cases this being the attending midwife.…”
Section: Methodsmentioning
confidence: 99%
“…11,13 All participants gave written informed consent for their clinical data and CTG files to be used for the purpose of research. No person-identifiable data were disclosed in the present study.…”
Section: Details Of Ethics Approvalmentioning
confidence: 99%